Teachersâ Education Curriculum towards Establishment of Patriotism in Malaysia - Ismail, Ramli; Wahab, Norwaliza Abdul (EDUCARE, 2013)
ABSTRACT: This study aims to identify and analyse the elements contained in the objectives of academic curriculum and co-curricular content in terms of differences, relationships, influences, and understanding of learning skills, thinking skills as a mediator to the confidence to apply the elements of patriotism among students of Post-Graduate Teaching Course for Primary School (PGTC PS) and Bachelor of Teaching for Primary Schools (BT PS) in Institute of Teachers Education (ITE) in Malaysia. This survey study used questionnaires on 289 PGTC PS and BT PS students of the North Zone and East Zone ITE in Peninsular Malaysia. The t-test results showed that there was a significant difference between PGTC PS and BT PS students in terms of understanding on learning skills and thinking skills, but do not have any significant difference in terms of confidence to implement the elements of patriotism. Pearson correlation analysis shows that there was a moderate relationship between the variables of learning skills, thinking skills, academic curriculum, co-curriculum, and the confidence to apply the elements of patriotism among PGTC PS and BT PS students. These findings serve as evidence to the Ministry of Education (MOE) in Malaysia to make recommendations to the ITE to serve as a guide in improving the confidence of trainee students in applying the elements of patriotism.KEY WORDS: Teaching the patriotism, learning skills, thinking skills, mediator, students, and Institute of Teachers Education in Malaysia.Â Â Â About the Authors: Dr. Ramli Ismail is a Lecturer at the Social Studies Department, Institute of Teachers Training, Sultan Mizan Campus, Besut, Terengganu, Malaysia; and Norwaliza Abdul Wahab is a Counsellor at the SMK (State Senior High School) Seri Pagi, Seremban, Negeri Sembilan, Malaysia. They can be reached at: rameysyis@gmail.com and lyzaalogan@gmail.comHow to cite this article? Ismail, Ramli & Norwaliza Abdul Wahab. (2013). âTeachersâ Education Curriculum towards Establishment of Patriotism in Malaysiaâ in EDUCARE: International Journal for Educational Studies, Vol.5(2) February, pp.173-190. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung, West Java; and FKIP UMP in Purwokerto, Central Java, ISSN 1979-7877.Chronicle of the article: Accepted (December 7, 2012); Revised (January 12, 2013); and Published (February 17, 2013).Â  Â